(untitled) (Papeles, 2017)
This paper is the result of a research that aims to know the perspective of some professors from the School of Economics at the National University of Colombia through the application of a questionnaire, in order to make a critical diagnosis, by analyzing the responses obtained, taking into account the concepts of acceptability, use, relevance and scientific nature that each one of the professors have about mathematics in economics . Besides, it also aims to make a theoretical review such as Gabriel Misas Arango, José Félix Cataño, among others.